2016
DOI: 10.1186/s12915-016-0282-1
|View full text |Cite
|
Sign up to set email alerts
|

MAPK signaling is necessary for neurogenesis in Nematostella vectensis

Abstract: BackgroundThe nerve net of Nematostella is generated using a conserved cascade of neurogenic transcription factors. For example, NvashA, a homolog of the achaete-scute family of basic helix-loop-helix transcription factors, is necessary and sufficient to specify a subset of embryonic neurons. However, positive regulators required for the expression of neurogenic transcription factors remain poorly understood.ResultsWe show that treatment with the MEK/MAPK inhibitor U0126 severely reduces the expression of know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 63 publications
3
75
0
1
Order By: Relevance
“…Interestingly, cWnt/TCF represses expression of the potential FGF ligand, fgf8A , in the central ring (animal hemisphere) restricting its expression to the central domain, suggesting a role of FGF induced ERK/MAPK signaling in endomesoderm formation [24]. However, a recent study that focuses on the role of ERK/MAPK signaling in the initiation of the neurogenic program in Nematostella development, suggest that FGFR might not be the (sole) activator of this pathway in the presumptive endomesoderm [35]. The same authors have also shown that pharmacologically inhibition of ERK/MAPK signaling using U0126, a potent inhibitor of the ERK activating kinase MEK [36,37], after fertilization blocks gastrulation and endomesoderm formation [35].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, cWnt/TCF represses expression of the potential FGF ligand, fgf8A , in the central ring (animal hemisphere) restricting its expression to the central domain, suggesting a role of FGF induced ERK/MAPK signaling in endomesoderm formation [24]. However, a recent study that focuses on the role of ERK/MAPK signaling in the initiation of the neurogenic program in Nematostella development, suggest that FGFR might not be the (sole) activator of this pathway in the presumptive endomesoderm [35]. The same authors have also shown that pharmacologically inhibition of ERK/MAPK signaling using U0126, a potent inhibitor of the ERK activating kinase MEK [36,37], after fertilization blocks gastrulation and endomesoderm formation [35].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study that focuses on the role of ERK/MAPK signaling in the initiation of the neurogenic program in Nematostella development, suggest that FGFR might not be the (sole) activator of this pathway in the presumptive endomesoderm [35]. The same authors have also shown that pharmacologically inhibition of ERK/MAPK signaling using U0126, a potent inhibitor of the ERK activating kinase MEK [36,37], after fertilization blocks gastrulation and endomesoderm formation [35]. As this treatment perturbs gene expression within the animal hemisphere as well as the apical domain, this further suggests a dual role of this pathway in germ layer formation and axial patterning [35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we found only one homolog of ERK1/2 in Nematostella , most resembling ERK2 (80.7% protein identity). To directly test the role of ERK2 and ERK5 signaling cascades in Hg-treated anemone we used the MEK1/2-specific inhibitor U0126, which was shown to inhibit ERK1/2 phosphorylation and activation in Nematostella [30, 31], the ERK5 inhibitor XMD 8-92 [48], or a combination of the two. Results showed that Hg induces Nematostella ERK2 phosphorylation and that U0126 completely inhibits ERK2 phosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 99%